2018
DOI: 10.1177/0038038518757953
|View full text |Cite
|
Sign up to set email alerts
|

‘Now She’s Just an Ordinary Baby’: The Birth of IVF in the British Press

Abstract: The birth of Louise Brown, the first baby born through in vitro fertilisation (IVF), in England in 1978 attracted worldwide media attention. This article examines how the contemporary British news media framed this momentous event. Drawing on the example of the Daily Mail’s coverage, it focuses on the way in which the British press depicted Louise’s parents’ emotions, marital relationship and social class in a context of political and economic crisis and resurgent social conservatism. The British press framed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…3 "Normality" and "normalization" is in many ways key to the global success of IVF, now the cornerstone technology of a multibillion-dollar fertility industry. Indeed, in the British press's coverage of Louise Brown's birth, the first "test tube baby" in 1978, the Brown's family normality was a key tenant of the media framing, thus setting up a dominant narrative of IVF stepping in to assist in conceiving children to ordinary folks, albeit in an extraordinary fashion (Dow 2019). Thompson (2005, 79-115) catalogues techniques of normalization in the fertility clinic, that is how "new material" is incorporated into preexisting grids of legibility.…”
Section: A Science Of Variation In the Normalizing Fertility Clinicmentioning
confidence: 99%
“…3 "Normality" and "normalization" is in many ways key to the global success of IVF, now the cornerstone technology of a multibillion-dollar fertility industry. Indeed, in the British press's coverage of Louise Brown's birth, the first "test tube baby" in 1978, the Brown's family normality was a key tenant of the media framing, thus setting up a dominant narrative of IVF stepping in to assist in conceiving children to ordinary folks, albeit in an extraordinary fashion (Dow 2019). Thompson (2005, 79-115) catalogues techniques of normalization in the fertility clinic, that is how "new material" is incorporated into preexisting grids of legibility.…”
Section: A Science Of Variation In the Normalizing Fertility Clinicmentioning
confidence: 99%
“…Yet the main resource is the vast printed (and increasingly digitized) record, from scientific journals and conference proceedings to glossy magazines and tabloid newspapers, and to a lesser extent television and radio broadcasts, interpretation of which has barely started (but see Van Dyck, 1995;Turney, 1998, pp. 166-187;and Dow, 2017and Dow, , 2019aand Dow, , 2019b; for an exemplary study, Nathoo, 2009;and for a general review, Hopwood et al, 2015). Analysis could, among many other things, bring several more patients from the Oldham programme into the picture (e.g., Bedford, 1970;New 'test tube' mother says: never again, 1970).…”
Section: From Personality To Public Figurementioning
confidence: 99%
“…In Figure 4.5, on the left edge, the law Vertices mutate as evidence accumulates; hence, a further bifurcation rises. In the intervening decades since her birth, the general public observed that Louise Brown grew to adulthood and eventually gave birth to two healthy babies [24,12]. The fear of unknown harm to IVF babies disappeared, while the demand for IVF services increased among fertility-challenged couples and among singles and same-sex couples [20].…”
Section: Step 6: Bifurcation and Policymentioning
confidence: 99%